Sequential analysis of optimal transmission switching with contingency assessment - Tarafdar Hagh, Mehrdad; Zamani Gargari, Milad; Vahid Pakdel, Mir Jalal (IET generation, transmission & distribution, 2018)
Optimal transmission switching (OTS) has been introduced as a persuasive approach for cost minimisation and the improvement of power system flexibility by utilising the lines’ existing conditions. Ordinary OTS based on optimal power flow (OPF) equations used in the previous studies may expose system security in some cases. This study proposes a novel sequential method to investigate the security of the system in post-OTS circumstances by considering N − 1 contingency criteria. The proposed method ranks the candidate lines as an operational strategy to reach the maximum reduction of the total operational cost by considering the security roles of transmission lines. The formulation of OTS and security assessment programs is based on alternating current OPF. The proposed approach provides more accurate solutions to a mixed integer non-linear programming model of the OTS program with N − 1 security criteria within a reasonable computation time. The obtained simulation results of the proposed method have been presented on IEEE 57-bus and IEEE 118-bus standard test systems. It is shown that the results of the ordinary OTS for lines’ outage ranking change because of system security consideration.